Distribution and Magnitude of Regional Volumetric Lung Strain and Its Modification by PEEP in Healthy Anesthetized and Mechanically Ventilated Dogs - Araos, Joaquin; Cruces, Pablo; Martin-Flores, Manuel; Donati, Pablo; Gleed, Robin D.; Boullhesen-Williams, Tomas; Perez, Agustin; Staffieri, Francesco; Retamal, Jaime; Vidal Melo, Marcos F.; Hurtado, Daniel E. (Frontiers in Veterinary Science, 2022)
The present study describes the magnitude and spatial distribution of lung strain in healthy anesthetized, mechanically ventilated dogs with and without positive end-expiratory pressure (PEEP). Total lung strain (LSTOTAL) has a dynamic (LSDYNAMIC) and a static (LSSTATIC) component. Due to lung heterogeneity, global lung strain may not accurately represent regional total tissue lung strain (TSTOTAL), which may also be described by a regional dynamic (TSDYNAMIC) and static (TSSTATIC) component. Six healthy anesthetized beagles (12.4 ± 1.4 kg body weight) were placed in dorsal recumbency and ventilated with a tidal volume of 15 ml/kg, respiratory rate of 15 bpm, and zero end-expiratory pressure (ZEEP). Respiratory system mechanics and full thoracic end-expiratory and end-inspiratory CT scan images were obtained at ZEEP. Thereafter, a PEEP of 5 cmH2O was set and respiratory system mechanics measurements and end-expiratory and end-inspiratory images were repeated. Computed lung volumes from CT scans were used to evaluate the global LSTOTAL, LSDYNAMIC and LSSTATIC during PEEP. During ZEEP, LSSTATIC was assumed zero, therefore LSTOTAL was the same as LSDYNAMIC. Image segmentation was applied to CT images to obtain maps of regional TSTOTAL, TSDYNAMIC, and TSSTATIC during PEEP, and TSDYNAMIC during ZEEP. Compliance increased (p = 0.013) and driving pressure decreased (p = 0.043) during PEEP. PEEP increased the end-expiratory lung volume (p < 0.001) and significantly reduced global LSDYNAMIC (33.4 ± 6.4% during ZEEP, 24.0 ± 4.6% during PEEP, p = 0.032). LSSTATIC by PEEP was larger than the reduction in LSDYNAMIC; therefore, LSTOTAL at PEEP was larger than LSDYNAMIC at ZEEP (p = 0.005). There was marked topographic heterogeneity of regional strains. PEEP induced a significant reduction in TSDYNAMIC in all lung regions (p < 0.05). Similar to global findings, PEEP-induced TSSTATIC was larger than the reduction in TSDYNAMIC; therefore, PEEP-induced TSTOTAL was larger than TSDYNAMIC at ZEEP. In conclusion, PEEP reduced both global and regional estimates of dynamic strain, but induced a large static strain. Given that lung injury has been mostly associated with tidal deformation, limiting dynamic strain may be an important clinical target in healthy and diseased lungs, but this requires further study.